Fuzzy-based MPPT algorithm implementation on FPGA chip for multi-channel photovoltaic system - Hanen Abbes; Hafedh Abid; Kais loukil; Mohamed Abid; Ahmad Toumi (Institute of Advanced Engineering and Science, 2022)
Microprocessors and microcontrollers are mostly used to control electrical systems. These chips front into problems while monitoring systems that need heavy computing and important processing. Likewise, they fail while handling inputs and outputs speeds, especially with multi-channel photovoltaic (PV) systems. In comparison to a digital signal processor (DSP) and microcontroller implementations, field programmable gate array (FPGA) device is able to integrate a great number of PV channels and to achieve short development time, cost less and more flexible operation. As well, new control algorithms are increasingly complex; using new performing technologies is very motivating. Mainly, FPGA technology is adopted thanks to its ability to control complex applications and intelligent laws. In opposition to traditional controls, fuzzy logic based control presents more efficiency and reliability response for non-linear systems. Therefore, this paper deals with the execution of the fuzzy-based maximum power point tracking (MPPT) technique by the means of the FPGA chip for a multi-channel photovoltaic system. A multi-channel photovoltaic system is designed. Then, the FPGA circuit is investigated to get benefits from this hardware solution. Since software implementation way integrates a limited number of PV panels, hardware implementation is a promising solution that reduces execution time and therefore controls a huge number of photovoltaic channels. Finally, results of simulation of the fuzzy technique implementation on FPGA chip show that the proposed PV system controls more than 4400 channels. Therefore, the system output power is increased and the system profitability is improved.